2013
DOI: 10.1371/journal.pone.0066122
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Drives Persistent Activity in Prefrontal Cortex via Synergistic α1 and α2 Adrenoceptors

Abstract: Optimal norepinephrine levels in the prefrontal cortex (PFC) increase delay-related firing and enhance working memory, whereas stress-related or pathologically high levels of norepinephrine are believed to inhibit working memory via α1 adrenoceptors. However, it has been shown that activation of Gq-coupled and phospholipase C-linked receptors can induce persistent firing, a cellular correlate of working memory, in cortical pyramidal neurons. Therefore, despite its importance in stress and cognition, the exact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 71 publications
7
83
3
Order By: Relevance
“…These data signify that the ␣ 1 -AR affects the striatum by delaying firing initiation and enhancing continued firing. Recently, it has been reported that noradrenaline drives persistent activity in rat prefrontal cortex via ␣ 1 -and ␣ 2 -ARs (Zhang et al, 2013). Although, at this moment, the precise roles of ␣ 1 -AR in the striatum are unknown, the enhancement of the late and post phase firing increment by phenylephrine is consistent with these reports.…”
Section: Slow Decay and Firing Incrementsupporting
confidence: 76%
“…These data signify that the ␣ 1 -AR affects the striatum by delaying firing initiation and enhancing continued firing. Recently, it has been reported that noradrenaline drives persistent activity in rat prefrontal cortex via ␣ 1 -and ␣ 2 -ARs (Zhang et al, 2013). Although, at this moment, the precise roles of ␣ 1 -AR in the striatum are unknown, the enhancement of the late and post phase firing increment by phenylephrine is consistent with these reports.…”
Section: Slow Decay and Firing Incrementsupporting
confidence: 76%
“…As mentioned in the Introduction, working memory is under tight control of catecholamine signaling in the PFC. In general, activation of D1Rs and α2ARs in the PFC facilitates working memory, while activation of α1ARs impairs these processes (Arnsten and Li, 2005, Arnsten, 2007, Hains and Arnsten, 2008, Zhang et al, 2013). Our finding that D1Rs and α1ARs reside together in PFC dendrites provides a potential neuroanatomical substrate for some opposing actions of these receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This long lasting depolarized state of neurons is evoked by stimulation of Gq-coupled receptors (mGluRs, muscarine Ach, 5-HT receptors) (Zhang et al, 2013) that results in the activation of the IP3 pathway and release of Ca ++ ions from the endoplasmic reticulum (Fowler et al, 2007). Elevation of the intracellular Ca ++ concentration activates the calcium-activated non selective cation current (iCAN) (Haj-Dahmane and Andrade, 1998), possibly mediated by the transient receptors potential channels (TRPCs) of both the prefrontal and entorhinal neurons (Fowler et al, 2007; Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%